2016
DOI: 10.1063/1.4942661
|View full text |Cite
|
Sign up to set email alerts
|

Thermal transport in Cu2ZnSnS4 thin films

Abstract: The stability of kesterite Cu2ZnSnS4 (CZTS) under a range of compositions leads to the formation of a number of stable defects that appear to be necessary for high efficiency photovoltaic applications. In this work, the impact of the presence of these defects on the thermal conductivity of CZTS thin films has been explored. Thermal conductivities of CZTS thin films, prepared by pulsed laser deposition with differing compositions, were measured from 80 K to room temperature using the 3ω-method. The temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Several other reports of wurtzite-type CZTS can be found, all reporting the use of DDT in the synthesis (Li et al, 2014;Mainz et al, 2014;Singh et al, 2013Singh et al, , 2012Zhou et al, 2015;Lu et al, 2011) and/or nanometredimensions (Azanza Ricardo et al, 2015;Syafiq et al, 2019). By cross-comparing results from different works, we noted a general higher abundance of wurtzite CZTS for grains with nanometre dimensions [<30 nm average dimensions (Li et al, 2014;Mainz et al, 2014;Singh et al, 2013Singh et al, , 2012Lu et al, 2011;Zhou et al, 2015;Azanza Ricardo et al, 2015)], while, for increasing domain size, the hexagonal phase seems to reduce to stacking faults (Kattan et al, 2015;Thompson et al, 2016;Engberg et al, 2020;Li et al, 2014;Syafiq et al, 2019) up to the point that neither (hexagonal arrangements nor faults) can be observed.…”
Section: Introductionmentioning
confidence: 79%
“…Several other reports of wurtzite-type CZTS can be found, all reporting the use of DDT in the synthesis (Li et al, 2014;Mainz et al, 2014;Singh et al, 2013Singh et al, , 2012Zhou et al, 2015;Lu et al, 2011) and/or nanometredimensions (Azanza Ricardo et al, 2015;Syafiq et al, 2019). By cross-comparing results from different works, we noted a general higher abundance of wurtzite CZTS for grains with nanometre dimensions [<30 nm average dimensions (Li et al, 2014;Mainz et al, 2014;Singh et al, 2013Singh et al, , 2012Lu et al, 2011;Zhou et al, 2015;Azanza Ricardo et al, 2015)], while, for increasing domain size, the hexagonal phase seems to reduce to stacking faults (Kattan et al, 2015;Thompson et al, 2016;Engberg et al, 2020;Li et al, 2014;Syafiq et al, 2019) up to the point that neither (hexagonal arrangements nor faults) can be observed.…”
Section: Introductionmentioning
confidence: 79%
“…The range for CZTS is defined by our measurements on d-CZTS (white stars, with error bars) and by previously published measurements on CZTS (white squares). All data besides d-CZTS are from the literature: (KBr) 1– x (KCN) x , PbTi x Zr 1– x O 3 (PZT), entropy-stabilized oxides (ESO), (KCl) 1– x (KBr) x , ordered and disordered FePt, and Si x Ge x . ,,,, The previously published CZTS data include the following: sintered powder (κ = 4.7 Wm –1 K –1 ); sintered nanocrystals (κ = 2.95 Wm –1 K –1 ); thin films, fully and incompletely sulfurized (κ = 4 and 0.9 Wm –1 K –1 , respectively) . The d-CZTS samples include low-gap samples grown at room- T and then annealed at temperature up to 450 °C and high-gap samples with growth temperature between room- T and 450 °C.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
“…A sharply defined shoulder on a particular diffraction peak (HKL) can indicate the presence of stacking faults with surface-normal direction {HKL}. ,, For CZTS, {112} is the close-packed direction (corresponding to {111} in high-temperature cubic unit cell), and the shoulder can be well-modeled as the result of a high concentration of stacking faults with {112} surface-normal. Here we show that our data are well-described by a model of CZTS with a high incidence of stacking faults along {112}.…”
Section: Experimental Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations